Anti-Inflammatory Activity of Ethanolic Extract Melophlus sp. and Callyspongia sp. from Southeast Sulawesi - Fristiohady, Adryan; Sahidin, Idin; Sadarun, Baru; Purnama, La O. M. J.; Rahmatika, Nur S.; Tien, Tien; Haruna, Lidya A.; Yodha, Agung W. M.; Wahyuni, Wahyuni (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Marine sponges display significant potencies as an anti-inflammatory agent. Thus this study aims to investigate the effect of anti-inflammatory of Melophlus sp. and Callyspongia sp. by decreasing plasma IL-1β levels of rats. This study was conducted by detecting chemical constituents of extracts and their anti-inflammatory by measuring the plasma IL-1β level of animals. Animals were acclimatized for seven days, followed at day-8 animals were induced by 1% carrageenan injection intraplantar. Animals were divided into ten groups (n=4) and treated orally according to groups which were C+ and K+ (diclofenac sodium 3598 ppm), C- and K- (Na CMC 0.5%), M50 (Melophlus sp 50 ppm), M100 (Melophlus sp 100 ppm), M200 ((Melophlus sp 200 ppm), C50 (Callyspongia sp. 50 ppm), C100 (Callyspongia sp. 100 ppm), and C200 (Callyspongia sp. 200 ppm). After being left out for 1 hour, blood was collected at the first, second, and third hour. Blood samples were then centrifugated and assayed with ELISA kit Rat IL-1β. Data collected were statistically analyzed. Both marine sponges contain flavonoid, saponin, alkaloid, and terpenoid. Tannin was only detected in Melophlus sp. Both marine sponges provided an effect in decreasing plasma IL-1β at the concentration of 100 ppm and 200 ppm. In conclusion, both extracts of Melophlus sp. and Callyspongia sp. have anti-inflammatory activity with effective concentration are 100 ppm. Keywords: Anti-Inflammatory; Plasma IL-1β; Melophlus sp.; Callyspongia sp.